A Wasted Day - Davis, Richard Harding, 1864-1916 (Salt Lake City, UT : Project Gutenberg, 2006)
"A Wasted Day" by Richard Harding Davis is a short story written during the early 20th century. This narrative unfolds around a wealthy businessman, Arnold Thorndike, who becomes unexpectedly involved in the life of a young man, Henry Spear, facing sentencing for theft. The story explores themes of compassion, the impact of social class, and the unexpected, often humorous consequences of good intentions. The plot centers on Thorndike's spontaneous decision to intervene on behalf of Spear, a former employee who found himself in trouble after a night of drinking. As Thorndike navigates through the unfamiliar setting of a courtroom, he witnesses the stark realities faced by those less fortunate than himself, which prompts a shift in his perspective. Throughout the proceedings, Thorndike$1 (Bs growing interest in the characters and their struggles reveals his desire to assist others, culminating in an acknowledgment of Spear's chances for redemption. The story concludes with Thorndike feeling a sense of fulfillment from his actions, despite the time he "wasted," highlighting the deeper value of human connection and the importance of lending a hand in the lives of others. (This is an automatically generated summary.)s
Release date is 2006-05-12
Produced by Don Lainson; David Widger
Keywords: Fiction; Short stories